PENILAIAN KINERJA KEUANGAN DAERAH PADA PEMERINTAH KABUPATEN KEPULAUAN ARU - Masidonda, Jaelani La; Sahupala, Jusuf; Baadilla, Julia Annadzmi (Politeknik Negeri Ambon, 2021)
This study aims to assess the financial performance of the Aru Islands Regency Region in 2017-2020. This research is a quantitative descriptive research, carried out at the Regional Financial and Asset Management Agency (BPKAD) of Aru Islands Regency. Data collection uses the documentation method. The data analysis technique uses regional financial ratio analysis. The results of the analysis show that the performance of the local government of Aru Islands Regency, seen from the ratio of independence, can be said to be low, meaning that the level of regional independence is low and still depends on revenue from the center. PAD financial effectiveness ratio can be categorized, not effective. Regional financial efficiency ratios are quite efficient. The ratio of compatibility between routine spending and development spending is not balanced. The PAD growth ratio experienced low growth. Keywords: Regional Financial Performance, Independence Ratio, Effectiveness, Efficiency, Harmony, and Growth.